Marketing Strategy of Island Tourism Development under Coronavirus Epidemic Marketing Strategy of Island Tourism Development under Coronavirus Epidemic case study of Nan’ao Island in China - Zhang, Shanli; Bi, Chuanchen (Technium Social Sciences Journal, 2023)
Affected by the new coronavirus pneumonia from the year 2019 to 2022, the economic development of the tourism industry was bleak. According to data released by the Ministry of Culture and Tourism, domestic tourism revenue in 2019 was 5.73 trillion yuan. In 2020, under the impact of the epidemic, the domestic tourism market has entered a low stage, with annual domestic tourism revenue of 2.23 trillion yuan, down 61.07 % year-on-year. Judging from the situation of people’s travel in recent years, the development of tourism is growing. Under the epidemic, the tourism industry was pressed the pause button and the expected recovery is full of uncertainty. The epidemic has brought great challenges to the tourism industry, but it is not impossible to break through. This will be a good time for transformation and upgrading. If the tourism industry wants to make more stable and better pace of development, more intelligent information construction services need to be created into it in order to achieve breakthrough and develop characteristic products. In the era of marine economy in the 21st century, island tourism is an important part of the marine industry group. It is favored because it gives tourists a psychological feeling of staying away from the hustle and bustle of the city and returning to nature completely. The island has become a popular attraction in the world. In view of this, it is of great significance to summarize the research on island tourism. Taking Nan’ao Island in Guangdong as an example, this paper analyzes the existing problems of island tourism and formulates corresponding marketing strategies, aiming at improving its competitiveness in the travel industry and forming differentiated competitive advantages.